Covid-19 Influence on Mixed Urban Cluster Air Quality: A Case Study from INDIA - Mahalingam, Sneha; Narayanan, Ramsundram (Asian Pacific Journal of Environment and Cancer, 2023)
Introduction: Policy decisions on containment of commercial activity to control the spread of COVID-19 SARS may influence urban air quality. Methodology: A methodological approach has been proposed to explore the relationship that exists between the policy decisions on six criteria pollutants (PM10, PM2.5, SO2, Ozone, NO2, and CO). This study also explores the knowledge /association that exists between the climatic variables, criteria pollutants, inhalation exposure dose levels and its vulnerable population age group and gender. The methodology explores a mixed urban cluster, Coimbatore, Tamilnadu, INDIA. Results: From the results, PM10, PM2.5, SO2 and CO has reduced to about 31%, 42%, 26% and 29% during phase-I, whereas NO2 (66%) and Ozone (14%) has increased. It is inferred that the reduced criteria pollutant load (during the phase I, II, and III) gets dispersed taking the advantage of geographical location. Conclusion: It is also observed that gender has an influence on the inhalation dose due to variability in inflow rate.